THE PROBLEMS OF THE CONSTITUTIONAL COURT'S DECISION NUMBER 65/PUU-XXI/2023 ON THE PERMISSION OF EDUCATIONAL INSTITUTIONS AS CAMPAIGN SITES - Luhukay, Roni Sulistyanto (Jurnal Meta-Yuridis, 2024)
According to the Republic of Indonesia's 1945 Constitution, the government is responsible for protecting the entire Indonesian nation and homeland, as well as improving the general welfare and intellectual life of the country through social justice principles. This mandate requires them to work toward the establishment of a national education system that maximizes his potential, possesses religious spiritual strength, self-control, personality, intelligence, noble character, and the skills required by himself, society, nation, and state. The presence of campaigns in educational institutions has the potential to cast a gloomy shadow over educational institutions that are currently mired in practical politics. To address this research, the author investigates normative research methods. The importance of allowing educational institutions to serve as campaign sites in accordance with the Constitutional Court's decision Number 65 / PUU-XXI / 2023, under the guise of developing political education in the learning process that attempts to understand citizens' rights and obligations in relation to good competencies. This takes the form of intellectual and participatory efforts to effectively form voter maturity in democracy in organizations, as well as the political skills of Indonesian youth, which can determine citizens' perspectives and attitudes toward democracy. On the other hand, this has implications for injustice and political campaign tendencies in educational institutions that use government facilities. Its use will not be evenly distributed among all political parties and candidates, as it will be determined by each participant's proximity to the local government. It is feared that regional heads will not be impartial because they are typically candidates from political parties that support or oppose one another. They have been given a seat, and using educational seats will be unfair to candidates with a high school education background. This is for the reason that it is certain that access to universities and Islamic boarding schools will be significantly limited compared to candidates with an S1 (bachelor's)or degrees or higher educational background. In order to prevent discrimination against campaign participants, graduates of Islamic boarding schools are also prohibited.